Media and Pictorial Reportage of Boko Haram Insurgency in Nigeria - Timothy Ekeledirichukwu Onyejelem; Perpetua Ogechi Aondover; Lawal Umar Maradun; Chioma Rose Chime-Nganya; Omolara Oluwabusayo Akin-Odukoya (Budapest International Research and Critics University, 2024)
Pictures are regarded as a universal means of communication. A good picture needs no translator as it fixes the mind more readily. It has a great advantage over the written word; it does not need to be translated. Thus, the media play an important role in information dissemination process in addition to its entertainment, education and enlightenment function. The media interpret issues and event that may have great impact on people and societies. Media are used in communicating information especially in times of crises and uncertainties thus; creating awareness about happenings around the world. The paper argues that the media and pictorial reportage of the Boko Haram insurgency in Nigeria plays a significant role in shaping public perception, awareness, and understanding of the crisis. Boko Haram, designated as a terrorist organization by several countries, including Nigeria and the United States, has carried out numerous attacks leading to widespread displacement, loss of lives, and destruction of property. Media outlets must balance the need for impactful reporting with ethical concerns, such as respecting the dignity of victims and avoiding sensationalism or graphic depictions that may cause further trauma. With limited access for traditional media, social media platforms have become crucial in sharing real-time updates and personal accounts from affected regions. The paper concludes that the mass media have a lot of influence in the use of pictures in reporting Boko Haram insurgency in Nigeria. In media practice, professional journalists play the role of a gate-keeper by gathering, analysing and disseminating news and information about people, events and issues in society.